PELATIHAN MENJADI DIRI REMAJA YANG HEBAT - Nurul Intan Tamara; Rachel Dwi Ardella; Fathya Nida; Intan Fitri Denisa Domo; Anisa Aviva Dila (Universitas Negeri Padang, 2023)
Adolescence is a period when the environment has a major influence on adolescent behavior. Even though adolescents have reached a stage of cognitive development sufficient to determine their own actions, the way adolescents determine their attitudes is heavily influenced by peer pressure. Self-knowledge is the ability of individuals, especially adolescents, to see the strengths and weaknesses that exist in them so that they can make the right response to tensions that arise from within and from outside. The purpose of the intervention he carried out was to find out the differences in selfknowledge that students had with the method based on this intervention consisting of 4 stages, namely need assessment to Counseling Guidance teachers, distribution of bullying questionnaires to students, Focus Group Discussion (FGD) with students, provide materials and games in team building. As many as 50 participants took part in the series of activities separately from the Science class which was the flagship class and the Social Sciences class. . The result of the intervention activities that have been carried out is that students feel a good perception of the aspects of thoughts and feelings in bullying